Gambar Allah Menurut Kejadian 1:26-28 dan Implikasinya bagi Pengembangan Artificial Intelligence - Andre Malau; Andrew Scott Brake (Sekolah Tinggi Theologia Jaffray, 2022)
AbstrakTujuan penulisan artikel ini adalah untuk menjelaskan makna gambar Allah menurut Kejadian 1:26-28 dan implikasinya terhadap pengembangan Artificial Intelligence. Adapun metode penulisan yang digunakan adalah analisis kualitatif dengan metode hermeneutik. Adapun metode hermeneutik yang dugunakan ialah hermeneutik terhadap Alkitab sebagai salah satu komponen teologi dalam mempelajari penafsiran Alkitab. Dari hasil analisis yang penulis lakukan didapati makna manusia sebagai gambar Allah adalah kemuliaan dari Allah kepada manusia dalam tanggung jawab menjadi wakil Allah di dunia. Pengajaran tentang gambar Allah dalam Kejadian 1:26-28 sangat menolong manusia untuk melihat kembali harkat martabat manusia sebagai ciptaan Allah yang diberi tugas untuk berkuasa atas dunia ini. Konsep manusia sebagai gambar Allah sangat relevan sebagai sikap kritis terhadap perkembangan AI yang mengancam harkat dan martabat manusia. AbstractThe purpose of writing this scientific paper is to explain the biblical study of the image of God according to Genesis 1:26-28 and its implications for the development of Artificial Intelligence. The writing method used is qualitative analysis with hermeneutic method. The meaning of man as the image of God is the noble task of man by being God's representative on earth. Humans receive a mandate from God to regulate life in a good direction, including in the development of Artificial Intelligence technology. Some of the implications that can be drawn from the changes are: The development of Artificial Intelligence should not deprive people of jobs. God gave the mandate to humans to rule over life, not over machines. The life of this world requires humans who are able to give moral judgment while machines to the highest level will not be able to have moral abilities. Second, the development of Artificial Intelligence should not be aimed at sexual gratification because Allah only created men and women to enjoy sexual relations and reproduce. Third, the development of Artificial Intelligence must not endanger human dominance because there is a risk in the occurrence of programming errors. Artificial Intelligence acts deviate from human desires and is detrimental to life.